PENGARUH CAPITAL INTENSITY, INTENSITAS PERSEDIAAN, DAN LEVERAGE TERHADAP AGRESIVITAS PAJAK (Studi Pada Perusahaan Pertambangan terdaftar IDX 2017-2021) - Syafrizal Syafrizal; Sugiyanto Sugiyanto (Sekolah Menengah Kejuruan (SMK) Pustek, 2022)
This study aims to test and empirically prove the effect of capital intensity, inventory intensity and leverage on tax aggressiveness. This research was conducted at companies listed on the IDX in 2017- 2021. The type of research used is associative quantitative. The population in this study were all mining 8 companies listed on the IDX in the period 5 years. The number of samples in this study were 40 samples obtained through the purposive sampling method. The data analysis technique used is panel data regression analysis using Eviews V.12 software. The results of this study indicate that capital intensity, inventory intensity and leverage have a significant effect on tax aggressiveness, capital intensity has an effect on tax aggressiveness, inventory intensity has no effect on tax aggressiveness, and leverage has effect on tax aggressiveness.